Quality of textbooks from the knowledge management perspective - Jozef Hvorecky; Lilla Korenova (Universidad Politécnica Salesiana, 2023)
The COVID-19 pandemic demonstrated the importance of textbooks. They helped the learners to continue their learning in time of lockdowns. The period also raised a question: What features has to have a textbook to support learning in learner's full or partial isolation? The objective is to identify textbook's concepts and style leading to the isolated learner's outcomes equivalent to those in-classroom education. The methodology has a qualitative approach; we confront subjects' learning objectives and textbooks' content, in particular, the presence of relevant explicit and tacit knowledge. Explicit knowledge is always present because it consists of texts, illustrations, etc. Authors may forget about or occasionally neglect tacit knowledge: best practices and heuristics. The learners then cannot receive their subject's holistic knowledge, because they are unable to complete mental lifts between Revised Bloom's Taxonomy's levels. As results key features of mental lifts are identified. Based on them, strategies helping to balance explicit and tacit knowledge necessary for achieving subject's learning objectives are provided. The appropriateness of the balancing strategies is discoursed using examples from two distant subjects: Poetry and Geometry. In a stepwise manner, these examples address all mental lifts and show how such sequences can expand the learner's knowledge. To conclude the discussion demonstrated the suitability of exploiting complete sets of mental lifts. The authors can use it to make certain that no relevant tacit knowledge will absent in their materials.